1994
DOI: 10.1210/mend.8.4.7519723
|View full text |Cite
|
Sign up to set email alerts
|

Mammary gland factor activated by prolactin on mammary epithelial cells and acute-phase response factor activated by interleukin-6 in liver cells share DNA binding and transactivation potential.

Abstract: We have studied transcription factors that are coupled to the activation of cytokine receptors in liver and in mammary epithelial cells. Interleukin-6 (IL-6) causes the rapid activation of the acute-phase response factor (APRF) in the liver of animals during acute inflammation and in cultured human hepatoma cells (HepG2) and induces the transcription of the acute-phase protein genes, e.g. alpha 2-macroglobulin (alpha 2-M). In the mammary gland and in cultured HC11 mammary epithelial cells, milk protein genes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

1995
1995
1997
1997

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 16 publications
1
27
0
1
Order By: Relevance
“…As our studies were being completed, our observation of a very rapid activation of MGF in HC11 cells was independently corroborated (40,41). HC11 cells, derived from COMMA-1D cell line, have been used for studies on the transcriptional regulation of ␤-casein gene expression.…”
Section: Mgf Is Rapidly Activated By Prl and Down-regulated During Camentioning
confidence: 60%
See 1 more Smart Citation
“…As our studies were being completed, our observation of a very rapid activation of MGF in HC11 cells was independently corroborated (40,41). HC11 cells, derived from COMMA-1D cell line, have been used for studies on the transcriptional regulation of ␤-casein gene expression.…”
Section: Mgf Is Rapidly Activated By Prl and Down-regulated During Camentioning
confidence: 60%
“…Furthermore, the induction of MGF by PRL must be accompanied by additional hormonal stimulation by glucocorticoids and insulin at confluence to activate ␤-casein gene expression (61,63). Additionally, it was observed that the activation of MGF in HC11 cells is not sufficient to stimulate the transcription from the promoter composed of multimeric MGF sites, whereas the same promoter is activated by IL-6 in HepG2 cells (40). Moreover, all studies on this cell line were conducted in the presence of serum.…”
Section: Mgf Is Rapidly Activated By Prl and Down-regulated During Camentioning
confidence: 99%
“…It has been established in tissue culture cells that mammary gland-specific factors (MGF) (now StatSa and StatSb) activate the (i-casein gene promoter that contains a GAS site (Schmitt-Ney et al 1991;Gouilleux et al 1994a;Standke et al 1994;Liu et al 1995;Moriggl et al 1996). Support for an in vivo role of STATs in milk protein gene expression comes from experiments with WAP (Li and Rosen 1995) and BLG (Burdon et al 1994) transgenes in which the GAS sites had been inactivated.…”
Section: Milk Protein Genes Are Expressed In Statsa-deficient Micementioning
confidence: 99%
“…The common denominator of these elements is their ability to bind a dimer of Stat 1, the gamma-interferon activation factor (GAF), [11]. However, GAS-like elements differ slightly in their DNA sequence and are thus capable of specific association with other different Stat proteins [12][13][14][15][16][17][18]. One of these GAS-like elements has originally been found in the promoters of genes that encode milk proteins and that are induced upon prolactin stimulation of mammary gland cells during lactation [19].…”
Section: Introductionmentioning
confidence: 99%